Specific land cover class mapping by semi-supervised weighted support vector machines - Silva, Joel (2017)
Silva, J., Bação, F., & Caetano, M. (2017). Specific land cover class mapping by semi-supervised weighted support vector machines. Remote Sensing, 9(2), [181]. https://doi.org/10.3390/rs9020181